Numerical Assessment of Ultra-high Performance Concrete Material - Yin, H. (Institute of Physics Publishing, 2017)
This paper presents numerical assessment of ultra-high performance concrete (UHPC) material using finite element (FE) method. Since UHPC is a relatively new material with superior strength and energy absorption, the concrete models on UHPC in FE analysis are not fully capturing behavior of UHPC. In this study, the calibration of concrete models for UHPC is exploited. The calibrated models show their capability to capture the response of UHPC material quite well compared with experiment. More details of results are discussed. © Published under licence by IOP Publishing Ltd.